EFEK MEDIASI MOTIVASI BELAJAR PADA PENGARUH REINFORCEMENT TERHADAP HASIL BELAJAR SISWA (Systematic Literature Review) - Melissa Delvia, - (2020)
Penelitian ini mengulas beberapa artikel tentang reinforcement yang dianggap memiliki pengaruh dalam meningkatkan motivasi belajar sekaligus hasil belajar siswa. Tujuan penelitian ini untuk mengetahui pengaruh reinforcement terhadap hasil belajar siswa serta efek mediasi motivasi belajar pada pengaruh reinforcement terhadap hasil belajar siswa. Metode penelitian yang digunakan adalah systematic literature review. Pencarian artikel relevan dilakukan pada publikasi online ResearchGate, PubMed, Semantic schoolar, Taylor and Prancis, World Wide Journal, Google Schoolar, Eurasia Journal of Mathematic sains and technology. Yang diterbitkan antara Tahun 2010-2020. Penulis memperoleh 13 artikel yang memenuhi syarat berdasarkan karakteristik pemilihan artikel relevan yang telah ditentukan. Temuan artikel menunjukan bahwa reinforcement memiliki pengaruh positif terhadap hasil belajar siswa. Hal ini disebabkan saat siswa diberikan reinforcement oleh guru maka pengetahuan yang terbentuk melalui ikatan stimulus dengan respon akan semakin kuat. Selain itu, ditemukan bahwa ketika reinforcement meningkat, maka tingkat motivasi belajarnya juga ikut meningkat, yang pada akhirnya akan meningkatkan hasil belajar siswa. Kata kunci: Reinforcement, Motivasi Belajar, Hasil belajar siswa. Melissa Delvia (1600714) "The Mediating effect of Learning Motivation on the impact of Reinforcement Toward Student Learning Outcomes (Systematic Literature Review)". Under Supervisor I: Dr. Moch Dudih Sugiharto, M.Si. and Supervisior II: Dr. Siti Parhah, S.Pd., M.SE. ABSTRACT This study reviews several articles about reinforcement which are considered to have an influence in increasing learning motivation as well as student learning outcomes. The purpose of this study was to determine the effect of reinforcement on student learning outcomes and the mediating effect of learning motivation on the effect of reinforcement on student learning outcomes. The research method used is systematic literature review. The search for relevant articles was carried out on the online publications ResearchGate, PubMed, Semantic schoolar, Taylor and France, World Wide Journal, Google Schoolar, Eurasia Journal of Mathematic science and technology. Published between 2010-2020. The author obtained 13 articles that meet the requirements based on the characteristics of the selection of relevant articles that have been determined. The findings of the article show that reinforcement has a positive effect on student learning outcomes. This is because when students are given reinforcement by the teacher, the knowledge formed through the binding of the stimulus with the response will be stronger. In addition, it was found that when reinforcement increased, the level of motivation to learn also increased, which in turn would improve student learning outcomes. Keywords : Reinforcement, Learning Motivation, Student Learning outcomes.